The Production and Distribution Systems of the Shea Crop in Northern Ghana: A Mixed-Methods Analysis of Value Chains and Sustainability - Abdul Kadir Adam; Himadri Barman (Program Studi Magister Agribisnis, Universitas Sebelas Maret, 2026)
This paper analyzes the shea value chain of Northern Ghana, from harvesting to marketing, and identifies its inefficiencies, key challenges, and socio-economic dynamics. The study adopts a mixed-methods approach, combining quantitative data from 402 value chain actors across four districts (Tolon/Kumbungu, Fumbisi, Savelugu/Nanton, and Sagnarigu) with a literature review. Variables such as landholding size, yield, education level, harvesting practices, production costs, and distribution satisfaction were analyzed using descriptive statistics, chi-square tests, Fisher’s exact test, Pearson correlation, linear regression, and ANOVA. The shea value chain is predominantly female-driven (94.8%) and heavily reliant on manual labor, with limited value addition and low market penetration. Key issues include small landholdings (67.4% ranging from 4–6 hectares), sustainability pressures (69.7% reporting a lack of shea trees), a strong reliance on local markets (78.4%), and high levels of dissatisfaction (68.9%). Significant relationships were found between landholding size and yield (Fisher’s exact test = 54.783, p < 0.001), production costs and landholding size (ANOVA F = 3.915, p = 0.004), and yield and harvesting practices (F = 2.961, p = 0.032). Major constraints include insecure land tenure (71.9%), equipment shortages (42.0%), and limited access to inputs (38.1%). Policy recommendations include land reform, increased investment in infrastructure, strengthening cooperatives, and developing gender-responsive programs